The Effect of Profitability And Liquidity on The Value of Non Cyclical Consumer Sector Companies Listed on The Indonesia Stock Exchange (IDX) In 2019-2023 - Yolanda, Nabila; Izzati, Dina; Zahrani, Vista; Delani, Maisya; Azzahra, An (Indonesian Journal Publisher, 2024)
The purpose of this study is to examine how productivity and liquidity affect the value of non-cyclical buyer division companies listed on the Indonesia Stock Exchange between 2019 and 2023. Return on Assets (ROA) is used in this study to quantify productivity, while the Debt to Equity Ratio (DER) is used to measure liquidity. Quantitative data that is based on reliable information from relevant firm budgeting explanations is employed. Different straight relapse is the explanatory technique linked, allowing researchers to identify significant relationships between the subordinate variable (firm esteem) and the autonomous components (ROA and DER). In addition to providing important information for financial experts and business management to use when making critical decisions, this study is expected to yield deep insights into how benefit and liquidity impact firm value. The results of this study are expected to enhance writing about factors that affect firm value and increase knowledge of the importance of controlling profitability and liquidity in advancing business performance in the capital display.